2007
DOI: 10.1093/ajcn/85.5.1286
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial whole-body protein metabolism after a meat meal is influenced by chewing efficiency in elderly subjects

Abstract: Meat proteins could be classified as fast digested proteins. However, this property depends on the chewing capacity of elderly subjects. This study showed that meat protein utilization for protein synthesis can be impaired by a decrease in the chewing efficiency of elderly subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 24 publications
2
82
0
3
Order By: Relevance
“…In line with the assumption that increasing the amount of meat ingested leads to a progressive increase in postprandial aminoacidemia, a moderate serving of meat (24 g protein) was insufficient to trigger a significant increase in postprandial muscle protein synthesis in elderly men (60 y), whereas a larger serving (36 g protein) of the same cooked ground beef triggered it (18). We previously showed that the utilization of meat protein for protein synthesis can be significantly impaired in the elderly by decreased chewing efficiency (7). Thus, the decrease in protein assimilation observed with RM compared with FCM when the meat is not minced could be accentuated in the elderly with poor dental status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the assumption that increasing the amount of meat ingested leads to a progressive increase in postprandial aminoacidemia, a moderate serving of meat (24 g protein) was insufficient to trigger a significant increase in postprandial muscle protein synthesis in elderly men (60 y), whereas a larger serving (36 g protein) of the same cooked ground beef triggered it (18). We previously showed that the utilization of meat protein for protein synthesis can be significantly impaired in the elderly by decreased chewing efficiency (7). Thus, the decrease in protein assimilation observed with RM compared with FCM when the meat is not minced could be accentuated in the elderly with poor dental status.…”
Section: Discussionmentioning
confidence: 99%
“…One of the nutritional strategies aimed at counteracting this anabolic resistance consists of using rapidly digested proteins (fast proteins) to exceed the stimulation threshold and trigger postprandial protein anabolism (6). We showed in a previous study that meat proteins can be considered as fast proteins (7). However, meat consumption generally decreases in older people (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete denture wearers tend to choose a diet that is low in protein, non-starch polysaccharides, calcium and vitamins 26 . Their inability to effectively comminute foodstuffs also has a negative effect on digestion 28,29 . On the other hand, Weiss and coworkers reported that a Body Mass Index (BMI) of 28 or above is associated with reduced morbidity and mortality in very old subjects 30 .…”
Section: The Benefits Of Retaining Natural Teeth Dietmentioning
confidence: 99%
“…It is possible that optimising chewing behaviour and the particle size distribution of the food bolus can benefit the glycaemic response (Ranawana, Henry, & Pratt, 2010;Read et al, 1986;Suzuki et al, 2005), amino acid assimilation (Remond et al, 2007), texture perception (Brown & Braxton, 2000;Brown, Langley, Martin, & Mac Fie, 1994), and the extent of flavour release (Alfonso, Neyraud, Blanc, Peyron, & Dransfield, 2002;Taylor, 1996).…”
Section: Introductionmentioning
confidence: 99%